The Platform Switching Approach to Optimize Split Crest Technique - G. Sammartino; V. Cerone; R. Gasparro; F. Riccitiello; O. Trosino (Case Reports in Dentistry)
The split crest technique is a reliable procedure used simultaneously in the implant positioning. In the literature some authors describe a secondary bone resorption as postoperative complication. The authors show how platform switching can be able to avoid secondary resorption as complication of split crest technique.